Prevalence of bovine fasciolosis in and around Bedelle - Wazir Shafi (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
The study was carried out, in Illubaboral zone of Oromia regional at western part of Ethiopia in Bedelle municipal abattoir from November 2010 to the end of March 2011, in order to determine the prevalence of liver fluke, the species of liver fluke and to compare the diagnostic efficiency of fecal and post mortem examination. Out of 384 livers and fecal samples examined 93(24.21%) and 74(19.27%) were positive of fasciolosis respectively. The most common liver fluke species affecting the cattle was Fasciola gigantica 52(13.54%) cattle were infected with Fasciola gigantica while, Fasciola hepatica were present in 31(8.07%) cattle and 10(2.6%) were mixed infection. There was a strong relationship between fecal examination and post mortem examination of liver lesions, but under local condition post mortem examination was considered a better diagnostic tool for fasciolosis. This study showed that there is no significant association (p>0.05) between the prevalence of age, body condition and origin of animal, but there is a significance difference (p<0.05) in prevalence of fasciola hepatica, between origin of animals.